The Other Half: An Examination of Monthly Food Pantry Cycles in the Context of SNAP Benefits. Issue 2 (28th January 2021) - Byrne, Anne T.; Just, David R.
Abstract: This study contributes to the growing literature on household resource allocation across time by examining monthly cycles of food pantry visitation. This study uses 13 years of data from over 40, 000 households who visited the Food Bank for Larimer County in Northern Colorado. Analysis reveals that pantry visitation fluctuates dramatically by day of the month and is highest at the end of the month among the general pantry client population. Further analysis examines these monthly cycles with consideration for the Colorado SNAP distribution schedule, with results that suggest pantry visitation increases when SNAP benefits run out. JEL CLASSIFICATION: D15 (Intertemporal Household Choice); Q18 (Food Policy)